ROLE OF ADDED CARBON NANOPARTICLES (CNTS) ON THE PROPERTIES OF MECHANISMS AND STRUCTURES MADE FROM AL-CU ALLOY - Aenas Laith Ali (Journals Park Publishing, 2026)
This research work is, therefore, devoted to investigating the mechanical and structural properties of an Al-Cu alloy due to the addition of different weight ratios of carbon nanotubes (0.5%, 1.0%, 1.5%, and 2.0%). The samples were prepared in an optimal way for a better dispersion of nanoparticles into the base materials. Tensile test and Vickers hardness test were conducted along with the wear resistance test in order to check the surface properties subjected to frictional force. Microstructural analysis was done by using SEM and an XRD analysis for identifying the crystal structure of the materials. The result of the tensile test has shown a substantial increase in tensile and yield strengths when adding up to a desired ratio and marked enhancement in the Vickers hardness values, signifying enhanced resistance against plastic deformation. The wear test result indicated the decrease in wear rate and groove formation with the increase in ratios of CNTs, signifying enhanced surface wear resistance properties. The SEM result indicated that the CNTs are well dispersed in the alloy with desired ratios, representing reduced grain size and improvement in the microstructure. There was noticeable agglomeration at a desired ratio of CNTs. The XRD test revealed the stability of the main phases (Al and Cu) with the secondary phases (Al₂Cu) but without the carbide phase (Al₄C₃). In addition, the broadening of the diffraction peaks with the increase in the CNTs content was observed. The addition of CNTs to the Al-Cu alloy resulted in an improvement in the mechanical properties and wear resistance of the alloy while ensuring the stability of the structure. This composite material can therefore be considered suitable for applications where lightweight materials with high mechanical properties are needed.
Keywords: CNTs, Al-Cu alloy, Metal-based composites (MMCs), nanocomposities, wear behavior.